THE ROLE OF TEACHERS IN LEARNING MEDIA TO IMPROVE COOPERATION BETWEEN STUDENTS IN ELEMENTARY SCHOOLS - Kamasiah; Karim; Iye, Risman; Yusnan, Muhammad (Lembaga Penelitian dan Pengabdian Masyarakat FKIP UMB, 2024)
Teachers have an important role in the use of learning media to improve cooperation between students in elementary schools. The purpose of this study is to determine the role of teachers in learning media to improve cooperation between students in grade IV of State Elementary School 2 Kaobula. This study uses a qualitative research type with a descriptive approach to explore the role of teachers in the use of learning media to improve cooperation in grade IV of State Elementary School 2 Kaobula. The descriptive approach was chosen because it allows for an in-depth analysis of the various strategies and techniques applied by teachers in utilizing learning media as a tool to encourage collaboration between students. The results of the study indicate that the role of teachers in the use of learning media is very important in improving student cooperation in grade IV of State Elementary School 2 Kaobula. Teachers not only design learning media that are interesting and in accordance with learning objectives, but also act as facilitators who guide students in working together. The use of interactive media such as educational videos, group games, and visual aids has been shown to increase student engagement and interaction in the learning process. With this strategy, the use of learning media not only improves students' academic understanding, but also strengthens their social skills, creating a more effective and enjoyable learning atmosphere.